Parameter study of boost inverter topologies for high voltage gain - Sabeeh, Saad Raad (2019)
To reducing electricity bills while reducing dependence on fossil fuels to generate electricity, the peoples use large amounts of solar energy. In addition to that, if the sunshine is available, that is the energy production depends on it, so that is beyond human control. The conventional Z-source network and switch inductor Z- source inverter is located between the DC voltage source and the inverter, which boosts the DC voltage. Traditional inverters such as voltage source inverters and current source inverters have few inherent limitations such as output voltage is limited to its input applied a voltage and usually, V-source inverters act like a buck converter, and likewise, I-source inverters operate as a boost converter. This two-stage configuration increases cost and reduces system efficiency. Also, the pass-through problem in the VSI and the open-circuit problem in the CSI are significant problems in system reliability. The structure proposed to overcome the above issues is a Z-source inverter (ZSI), which has a single-stage power conversion and a buck-boost voltage capability, unlike VSI and CSI inverters. On the other side, developing control technic is more complicated than that of the traditional inverters. For generating shoot through boost voltage, A DC envelope is introduced with the carrier signals to compare with it and make boost through zero state PWM signals, which have to be added with the traditional Modulated PWM, that are usually generated through comparison of the modulating sine wave with the carrier wave. In this research, the main objective is to designs a Z-source network circuit, SL Z-source inverter and embed with traditional single-phase H-bridge and to develop control logic, that would supply SPWM switching signals to IGBT gates. For this project, Simple constant boost control strategy has been developed and simulated in MATLAB / Simulink. For analysis, THD of the conventional Z-source inverter is 2.3% while THD for SL Z-source inverter is 1.44% and compare them see that the total harmonic distortion is better than traditional and also the boost factor and capacitor voltage stress are higher than conventional circuit when using same duty cycle and input voltage DC.